Perceptual and Contextual Sources of Athletic Training Confidence: The Transition to Professional Entry Level Master's Programs - Craig E. Pfeifer; Erin Moore; Brian Seiler; Caroline Thomason; Eva V. Monsma (Bowling Green State University, 2019)
Introduction: The shift of athletic training education from undergraduate degrees to professional master's degrees and the prominence of computer-based credentialing may impact the hands-on experiences beneficial for developing confidence in athletic training competency domains. Health care provider confidence is critical for clinical skill development, performance and enhancing patient care. Purpose: To examine domain specific efficacy, its sources, learning contexts (i.e., classroom, laboratory, clinical settings) and clinical characteristics by program types. Method: Descriptive, cross-sectional design where 178 Athletic Trainers (AT; age 24.25 + 3.76, n = 72 male, n = 106 female) participated in the study (Master's Program (MP) = 38; Undergraduate Program (UG) = 140). A questionnaire examining athletic training confidence was administered throughout multiple universities with accredited athletic training programs. Background characteristics, certification exam attempts, and programmatic characteristics were also ascertained. Results: Clinical settings were similar in both program types and there were few differences in domain-specific efficacy. Imaginal experiences, verbal persuasion and emotional states sources of efficacy differentiated master's from undergraduate students. Conclusions: Sources of efficacy (e.g. vicarious experiences) occur naturally in athletic training educational settings; however, these sources need to be utilized. Educators should be informed about efficacy sources and devise strategies targeting each source for implementation across evolving learning contexts.